Whiteness, Colonial Apathy, and (Micro)aggressions: Zwarte Piet as Cultural Heritage and a Device of Racial Violence (Cadernos de Sociomuseologia, 2025)
This article proposes a discussion and interconnection of the concepts of whiteness, colonial aphasia and microaggressions, articulated through a critical analysis of the cultural tradition of Sinterklaas and Zwarte Piet, understood as a form of cultural heritage in the Netherlands. The analysis argues that the maintenance of this alleged tradition functions as a symbolic device of racial violence, legitimised by discourses of innocence, supposed neutrality and the defence of cultural preservation, thereby reifying and contributing to the maintenance of the privileges of whiteness while disregarding, delegitimising and inferiorising the numerous interventions that denounce the violence and aggression enacted under the supposed mask of cultural tradition. In this sense, the article seeks to show how colonial aphasia and everyday (micro)aggressions operate in the naturalisation of racist practices in daily life, cloaked in the presumed normality of dominant groups that sustain the privileges of whiteness and the broader structure of coloniality. Finally, the article argues for the centrality of voices that have been historically subalternised in denouncing this reality and in producing forms of resistance, understanding them as crucial for transforming colonial legacies and for constructing cultural practices that value equality, equity and human rights.Keywords: whiteness; colonial aphasia; microaggressions; Zwarte Piet; cultural tradition